Effect of temperature and relative humidity on some biological traits of two Trichogramma cacoeciae (Marchal) (Hymenoptera: Trichogrammatidae) strains - Cheirf, Asma; Alloui-Griza, Rafika; Hached, Wiem; GRISSA-LEBDI, KAOUTHAR (African Entomology, 2025)
Temperature and relative humidity are key factors affecting the physiological and behavioural responses of natural enemies, including Trichogramma parasitoids frequently employed as biological control agents. Here, the effect of three temperatures (25, 30 and 35 °C) and relative humidity levels (10, 75 and 100%) on the fitness of two Trichogramma cacoeciae (Marchal) strains (Tunisian/Italian) were evaluated. Results indicated that temperature and relative humidity influenced all life-history parameters of parasitoids. Parasitism of the G0 generation by the Tunisian strain was higher compared to that of the Italian strain at 30 °C (10% RH) (22.33 ± 5.94 and 16.46 ± 6.45, respectively, for the Tunisian and Italian strain) and 35 °C (75% RH) (16.26 ± 5.11 and 11.33 ± 5.81, respectively, for the Tunisian and Italian strain). Furthermore, the parasitism rate is better in the G1 compared to the G0 generation only for the Italian strain at 25–30 °C and at 10, 75 and 100% RH. Emergence was significantly decreased for both strains at 35 °C regardless of the relative humidity level. For the G1 generation, no parasitism and emergence were shown by the Italian strain at 35 °C for all tested relative humidities. Our data indicate the Tunisian strain is adapted to higher temperatures. The implications of these results to improve the biological control of lepidopteran pests are discussed.